God and race : a guide for moving beyond black fists and white knuckles - Siebeling, John, 1967-; Francis, Wayne (Pastor) (HarperOne, an imprint of HarperCollinsPublishers, 2022)
"A White pastor and a Black pastor, close friends who have each built racially diverse congregations, offer a model Christians can follow to open necessary conversations about race, encourage unity, and foster mutual respect to heal a wounded nation riven by racial tension and political tribalism. For years, Pastors John Siebeling and Wayne Francis have led thriving congregations that are the embodiment of diversity; Siebeling in Memphis and Francis in New York City. Many churches and leaders have sought their counsel, hoping to emulate their success. At the height of the Black Lives Matter protests in Summer 2020, they pooled their insights and experiences to help others facilitate conversations about racism. The guide they developed is the basis of God and Race. Siebeling and Francis examine the White-Black tension from both perspectives and answer all the uncomfortable questions we're afraid to ask--regarding ourselves, our families, our work and relationships, and the church. Most important, they provide practical steps anyone can take to become part of the solution. Whether you are a church leader or just a caring person who wants to make a difference, God and Race provides inspiration and guidance to help you become an agent of reconciliation and change. These two wise pastors teach you how to find your voice and join Jesus in healing, to help bring our divided communities together with open minds, open hearts, and open hands. Many Christian books on race either do not ask the hard questions or, if they do, speak as critics outside the mainstream church. Siebeling and Francis probe the meaning of racial reconciliation and reveal how the church can be a positive and effective leader to move us forward, beyond hate and injustice, to equality and love." --